Women in Tourism and Hospitality - A Case Study of Bhaktapur (Journal of Tourism & Adventure, 2022)
Globally more women are employed in tourism and hospitality industry which is also a very lucrative means to achieve gender equality, women empowerment and socio-economic upliftment of women. Empowerment of women and tourism are interrelated, and both terms should be developed side by side for better future. However, the gender-based roles in tourism and hospitality are defined by the nature of work along with the requirements of tourist. As far as Bhaktapur is concerned, tourism is one of the main sectors in the state that contributes in income and employment to people. This study explores the contribution of women in tourism and hospitality industry in Bhaktapur. Various aspects have been explored such as women employed in various hospitality and tourism sectors, the total number of women employed, category and duration of jobs, socio-economical upliftment. The main information is based on numerous sources of social learning like field visits while doing researches, visit of different sites, focus on group discussions, General Questionnaire Survey, and a number of interviews and interactions with the professionals of tourism sector in Bhaktapur.